Development of invasive pink salmon (Oncorhynchus gorbuscha Walbaum) eggs in a large Barents Sea river. Issue 4 (23rd July 2022) - Erkinaro, Jaakko; Orell, Panu; Pohjola, Jan‐Peter; Kytökorpi, Mikko; Pulkkinen, Henni; Kuusela, Jorma
Abstract: The spawning and egg development of invasive pink salmon Oncorhynchus gorbuscha were investigated in the large River Teno in the Barents Sea area where they spawned for the first time on a large scale in 2021. The spawning period started in early August and egg development was rapid. All eggs were eyed by mid‐September and the first juveniles hatched in late September. In early October most eggs had hatched. Degree‐days in water temperature suggested that egg deposition had mostly taken place in early August. Early egg development is discussed in relation to possible consequences for survival.